Combining conventional ultrasound and ultrasound elastography to predict HER2 status in patients with breast cancer - Zhuo, Xiaoying; Lv, Ji; Chen, Binjie; Liu, Jia; Luo, Yujie; Liu, Jie; Xie, Xiaowei; Lu, Jiao; Zhao, Ningjun (Frontiers in Physiology, 2023)
Identifying the HER2 status of breast cancer patients is important for treatment options. Previous studies have shown that ultrasound features are closely related to the subtype of breast cancer. In this study, we used features of conventional ultrasound and ultrasound elastography to predict HER2 status. The performance of model (AUROC) with features of conventional ultrasound and ultrasound elastography is higher than that of the model with features of conventional ultrasound (0.82 vs 0.53). The SHAP method was used to explore the interpretability of the models. Compared with HER2tumors, HER2+ tumors usually have greater elastic modulus parameters and microcalcifications. Therefore, we concluded that the features of conventional ultrasound combined with ultrasound elastography could improve the accuracy for predicting HER2 status.